How innovation works - Ridley, Matt. (London 4th Estate, 2020)
Innovation is the main event of the modern age, the reason we experience both dramatic improvements in our living standards and unsettling changes in our society. It is innovation that will shape the twenty-first century. Yet innovation remains a mysterious process, poorly understood by policy makers and businessmen alike.
Includes bibliographical references and index
Keywords: Technological innovations -- History; Technological innovations -- Economic aspects; Social change -- History